2014
DOI: 10.3233/wor-121579
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of positioning to work-related musculoskeletal discomfort in diagnostic medical sonographers

Abstract: Background Musculoskeletal pain and discomfort due to work exposure is experienced by 90% of sonographers. Survey research has provided a wealth of information to document this problem, but few studies have attempted to directly measure and identify the source of these disorders. Objective This pilot observational study was conducted to obtain direct measures of the relationship of sonographers to their environment during the completion of sonographic examinations. Methods The Rapid Upper Limb Assessment (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 17 publications
0
30
0
Order By: Relevance
“…The mean duration of WRMDs reported was 30.48 months (ranging from 2 to 120 months), which affects daily routine life of 64.22% Sonographer. To know the severity of pain visual analogue score (VAS) on Likert Scale from 1-10 was used, however for statistical purpose the variable was converted into ordinal as mild (1 -4), moderate (5-7) and severe (8)(9)(10). Overall the WRMDs disorder was reported as severe by 45.9%, moderate by 33% and mild by 21% of the participants.…”
Section: *=Chi Square Test ¶= T-test Musculoskeletal Symptomsmentioning
confidence: 99%
“…The mean duration of WRMDs reported was 30.48 months (ranging from 2 to 120 months), which affects daily routine life of 64.22% Sonographer. To know the severity of pain visual analogue score (VAS) on Likert Scale from 1-10 was used, however for statistical purpose the variable was converted into ordinal as mild (1 -4), moderate (5-7) and severe (8)(9)(10). Overall the WRMDs disorder was reported as severe by 45.9%, moderate by 33% and mild by 21% of the participants.…”
Section: *=Chi Square Test ¶= T-test Musculoskeletal Symptomsmentioning
confidence: 99%
“…Conclusions drawn from this research suggested that to reduce WRMSDS, specific risk factors and ergonomic solutions must be identified for each type of scan. 22 A study by Roll et al 23 collected observational data using the Rapid Upper Limb Assessment (RULA), a tool that produces a score from 0 to 7 indicating the degree of exposure to physical risk. Their results determined that the participants noted a RULA score of 0.67 at the beginning of the day and a score of 2.38 at the end of the day, indicating that pain increased throughout each participant's workday.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Employer related costs, from both direct and indirect measures, has been estimated to be 120 billion US dollars each year. In fact, just absenteeism and lost work time alone cost employers approximately $21 153/week according to Roll et al [5]. Recognition of this condition is vital, as it can only be prevented and addressed once it is acknowledged and prioritized.…”
Section: These Views Do Not Represent the Views Of The United States mentioning
confidence: 99%